2002
DOI: 10.1034/j.1398-9995.2002.1s3412.x
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy is a matter of geography after all: sesame as a major cause of severe IgE-mediated food allergic reactions among infants and young children in Israel

Abstract: We found sesame to be a major cause of IgE-mediated food allergy in Israel. In fact, it is second only to cow's milk as a cause of anaphylaxis. We recommend that testing for food allergens be tailored to each community based on local experience and should include sesame in appropriate populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
7
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(165 citation statements)
references
References 26 publications
4
146
7
3
Order By: Relevance
“…Sensitisation rates based on positive SPT ranged from 0.3 % ) to 8.6 % (Arbes et al, 2005), and on specific IgE levels between 7.6 % (Liu AH et al, 2010) and 13.5 % . Lower rates were reported when clinical history and positive SPT were used for diagnosis, ranging from zero (Dalal et al, 2002) to 0.4 % (Woods et al, 2002). Only one study outside Europe used OFC and reported a prevalence of peanut allergy of 2.9 % in a group of Australian children 12 to 15 months old (Osborne et al, 2011).…”
Section: Outside Europementioning
confidence: 99%
“…Sensitisation rates based on positive SPT ranged from 0.3 % ) to 8.6 % (Arbes et al, 2005), and on specific IgE levels between 7.6 % (Liu AH et al, 2010) and 13.5 % . Lower rates were reported when clinical history and positive SPT were used for diagnosis, ranging from zero (Dalal et al, 2002) to 0.4 % (Woods et al, 2002). Only one study outside Europe used OFC and reported a prevalence of peanut allergy of 2.9 % in a group of Australian children 12 to 15 months old (Osborne et al, 2011).…”
Section: Outside Europementioning
confidence: 99%
“…Food allergy is an adverse immune reaction to food that depends on various factors such as diet and culture (Dalal et al, 2002), route of exposure, the genetic makeup of susceptible individuals (Bischoff & Crowe, 2005) and the inherent properties of the allergen itself (Breiteneder & Mills, 2005). Various biochemical and biophysical characteristics, such as thermal stability, pH stability, resistance to proteolysis, ligand interaction etc.…”
Section: Introductionmentioning
confidence: 99%
“…2). Sesame is a major cause of food allergy in some countries (Dalal et al 2002;Osborne et al 2011) and may be increasingly common in the US (Zuidmeer et al 2008). Stutius et al (2010) found that only 9 out of 69 patients with peanut allergies were also sensitive to sesame (Table 5).…”
Section: Pistachios and Cashewsmentioning
confidence: 99%